Pengembangan Sistem Informasi Penjualan Pakaian Wanita Menggunakan Metode Rapid Application Development (Rad) Berbasis Web Pada Inntsyourlove - Adrian Chandra Kusumah; Genta Aldora Leopriandis (Journal of Information Systems and Business Technology, 2025)
Using the Rapid Application Development (RAD) method, the objective of this study is to create a web-based women's clothing sales information system for INNTSYOURLOVE. INNTSYOURLOVE is a small micro business that still uses manual sales methods such as order recording and social media promotion, which can cause errors and slow down operations. The business requires a system that can improve operational efficiency, expand market reach, and provide faster and more responsive customer service due to the increasing use of information technology and the trend toward online shopping. The Rapid Application Development (RAD) method was chosen because it is iterative and adaptive, enabling system development in a shorter timeframe through continuous prototyping. The system uses HTML, CSS, and JavaScript to display key features such as a product catalog, homepage, contact information, and live chat. To ensure that all user interface features function properly, the black box method was employed. Although the system is not yet connected to a database and lacks a back-end, the development results demonstrate that the system can accelerate customer ordering processes and support INNTSYOURLOVE's digital transformation. It is recommended to continue development by adding a database, authentication system, and security features.